What Is God’s Speech (Kalāmullāh): Fakhr Al-Dīn Al-Rāzī’s Philosophical Solution to A Theological Disagreement - Tohir Mustofa (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2023)
Centuries after the miḥnah, the problem of the status of the Qurʿān and God’s speech in general persisted as a crucial theological problem discussed among Muslim theologians. This study examines the solution to this debate suggested by Fakhr al-Dīn al-Rāzī (d. 606/1210), an Ashʿarite-Shafiʿite theologian, with special reference to his book Khalq al-Qurʾān Bayn al-Muʿtazilah Wa Ahl al-Sunnah. It aims principally to discuss how al-Rāzī responds to the objections from his opponents on the nature of God’s speech, its uniqueness, and its pre-eternity. This research found that despite his affiliation to Ashʿarite school, al-Rāzī took a more moderate position towards the Muʿtazilah compared to his predecessors. He accepts the argument of the Muʿtazilah school that is built on the different conceptions of speech (kalām). We also found that the main key to understanding the debate between the pre-eternity or adventitiousness of God’s speech, including the Qur’ān, derived principally from the definition of speech itself. Rāzī does not reject the createdness of the external dimension of God’s speech, but he defends that its inner dimension (kalām nafs) is eternal. Furthermore, al-Rāzī also does not hesitate to borrow the falsafa theory to solve the problem of the pre-eternity of kalām as God’s attribute.